PERCEPTIONS OF THE NURSING TEAM TO THE PATIENT OUTSIDE THERAPEUTIC POSSIBILITIES - Barros, Renata Natoeli dos Santos (2017)
Care for individuals with terminal illness is a health care model that has been called "palliative care". It is essential to learn to cope with the loss in the context of non-prognosis disease. The study aims to identify and describe the nursing staff perceptions of the patient out of therapeutic possibilities. This is a literature review in national publications databases in the last ten years. Data analysis was performed by Minayo categorization technique (2012), in which it was possible to identify three categories. Given the literature, it was observed that the professionals have permeated situations of hardship, sorrow and suffering by patients and families. We conclude that at times, professionals are affected by the same sentiments, and what differentiates the approach adopted depends on the concepts and beliefs of each with the situation.